A New approach to Design and Implementation of IBM PC for Accessing Library CD-ROM Database via Campus Network - Chen, Ruey-Shun; Chen, D.J.; YEH, Y.S. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
Library CD-ROM with its enormous storage, retrieval capabilities and reasonable price, has been gradually replacing some of its printed counterparts. One of the greatest limitations on the use of stand-alone CD-ROM workstations, however, is that only one user can access the CD-ROM database at a time. This paper proposes a new approach to solving this problem.